Parkinson’s Disease: Carbidopa, Nausea, and Dyskinesia [Expression of Concern] - Hinz M; Stein A; Cole T (Dove Medical Press, 2020)
Hinz M, Stein A, Cole T. Clin Pharmacol Adv Appl. 2014;6:189–194. The Editor-in-Chief and Publisher of Clinical Pharmacology: Advances and Applications wish to issue an Expression of Concern for the published article. Concerns have been raised regarding the alleged undisclosed competing interests of some of the authors and alleged excessive self-citation for the published article. Clinical Pharmacology: Advances and Applications would like to alert readers of this while our investigation is still ongoing and we will provide an update following the conclusion of our investigation. The authors have been informed of these concerns and of our investigation. Read the original article